Introduction - Costa, Alex Aparecido da (Romanitas - Revista de Estudos Grecolatinos, 2022)
Introduction to the dossier: "Periphery, subalterns and power relations in the Ancient World".
Keywords: Introduction; Dossier; Periphery; Subalterns; Ancient World